PENGARUH KEMISKINAN, INFLASI, TENAGA KERJA, EKSPOR, KONSUMSI DAN INVESTASI TERHADAP PRODUK DOMESTIK REGIONAL BRUTO SUMATERA UTARA - Jefferson Lowie; Sunarji Harahap; Elidawati Elidawati; Thomas Sumarson Goh (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2023)
The purpose of this study was to determine and analyze the effect of poverty, inflation, labor, exports, consumption and investment on the gross regional domestic product of North Sumatra. The population of this study is 33 data on poverty, inflation, labor, exports, consumption, investment and gross regional domestic product of North Sumatra for the period 2017-2020. The sample of this study is 33 data on poverty, inflation, labor, exports, consumption, investment and products. North Sumatra's gross regional domestic product for the period 2017 - 2020. The data collection technique is based on the documentation on the data presented on the website https://sumut.bps.go.id/site/selectdata.html. This study uses multiple linear regression analysis. The results showed that poverty had no effect on the grossw regional domestic product of North Sumatra. Inflation has no effect on the gross regional domestic product of North Sumatra.